Catalogue of the Cerambycidae (Coleoptera) of the Neotropical Region. Part III. Subfamilies Parandrinae, Prioninae, Anoplodermatinae, Aseminae, Spondylidinae, Lepturinae, Oxypeltinae, and addenda to the Cerambycinae and Lamiinae - Monné, Miguel A. (Zootaxa, 2006)
A catalogue of the subfamilies Parandrinae (two tribes, four genera and 39 species), Prioninae (nine tribes, 83 genera, 309 species and 13 subspecies), Anoplodermatinae (three tribes, 10 genera and 27 species), Aseminae (two tribes, five genera, 18 species and two subspecies), Oxypeltinae (two genera and three species), Spondylidinae (one genus and one species) and Lepturinae (two tribes, 51 genera, 237 species and two subspecies) (Coleoptera: Cerambycidae) of the Neotropical Region is presented. Under each family-group name bibliographical references are given and under each species-group name, data on the type-locality, the acronym of the institution where the type is deposited, the geographical distribution and detailed bibliographical references are provided. In Prioninae, Callipogonini: Anacanthus Audinet-Serville, 1832, preoccupied by Anacanthus Gray, 1830 (Pisces) is substituted by Chorenta Gistel, 1848. In Lepturinae, Lepturini: Euryptera virgata Gounelle, 1911, new status; Necydalini: Platynocera Blanchard, 1851, preoccupied by Platynocera Blanchard, 1847, Coleoptera, Chrysomelidae is substituted by Stenorhopalus Blanchard, 1851. Omissions to Monné (2005a, b) are given in the addenda. The following taxa described before February 2005 were absent and now are included: Cotyachryson inspergatus (Fairmaire & Germain, 1859), new comb. in Achrysonini, Urorcites Thomson, 1878 in Elaphidiini, Areotis Bates, 1867 in Graciliini, Limernaea Thomson, 1878 in Hesperophanini, Trichoplon Martins, 1967 in Ibidionini, Ischasia ecclinusae, I. mareki, I. pouteriae, I. sabatieri, I. viridithorax, Ommata (Ommata) gallardi, Ommata (Eclipta) bauhiniae, O. (E.) giuglarisi, O. (E.) guianensis, O. (E.) kawensis, O. (E.) lauraceae, O. (E.) pilosipes, O. (E.) vasconezi, Ommata (Rhopalessa) durantoni, Phygopoda ingae, in Rhinotragini, all Peñaherrera-Leiva & Tavakilian, 2004, Epipodocarpus Bosq, 1951 in Tillomorphini and in Trachyderini, Trachyderina, Vianauragus, new name for Uragus Guérin-Méneville, 1844, not Uragus Keyserling & Blasius, 1840, Aves. The following new names are given, in Achrysonini: Achryson jolyi, new name to replace Achryson concolor Joly, 2000 preoccupied by Achryson concolor LeConte, 1873 (Geropa) and Cerdaia new name to replace Pehuenia Cerda, 1980, preoccupied by Pehuenia Roth, 1902, extinct Mammalia; in Elaphidiini: Anelaphus martinsi, new name to replace Anelaphus fasciatus Martins, 2005, preoccupied by Anelaphus fasciatus (Fisher, 1932); in Rhopalophorini: Rhopaliella new name to replace Rhopalina Monné, 1990, preoccupied by Rhopalina Tinkham, 1939, Orthoptera; in Trachyderini, Trachyderina: Chemsakiella new name to replace Linsleyella Chemsak, 1984, preoccupied by Linsleyella Rohr, 1980, Mollusca, Laneiella new name to replace Pujolia Lane, 1973, preoccupied by Pujolia Levasseur, 1968, Coleoptera, Neomegaderus new name to replace Megaderus Dejean, 1821, preoccupied by Megaderus Rafinesque, 1815, Pisces; in Incertae Sedis: Tippmannia new name to replace Dolichopterus Tippmann, 1953, preoccupied by Dolichopterus Hall, 1859, Eurypterida. One new synonym is proposed: Championa chemsaki Martins & Napp, 1992 = Championa bifasciata Noguera & Chemsak, 1997.